Challenges in Developing Productive Waqf Based on Masjid in Indonesia using Analytic Network Process (ANP) - Andi Triyawan (TSAQAFAH, 2023)
The purpose of this study is to analyze the priority problems and main solutions in the development of mosque-based productive waqf. The method used in this research is the Analytic Network Process (ANP). Respondents in this study came from practitioners and experts in Waqf. The results of this study indicate that after analyzing the results of interviews with expert resource persons and mosque managers. The priority problem in human resources is the ta'mir's understanding of productive waqf is still lacking with a geometric mean value shown of 0.46 while for institutional and government problems it shows that the lack of BWI's role in socializing and educating about productive waqf and local government is also less than optimal. Meanwhile, the priority solution is to provide education for productive waqf and its management for all ta'mir mosques and BWI also provides assistance and the government also provides support in the form of policies that can encourage the development of mosque-based productive waqf.